Marine bacteria from the Gulf of California with antimicrofouling activity against colonizing bacteria and microalgae - Sánchez-Rodríguez, Diana Elizabeth; Ortiz-Aguirre, Ismael; Aguila-Ramírez, Ruth Noemí; Rico-Virgen, Erika Guadalupe; González-Acosta, Bárbara; Hellio, Claire (Revista de Biología Tropical, 2018)
One way of reducing the input of pollutants into the marine environment is to enforce the use of non-toxic antifouling paints in marine protected areas. Thus, the purpose of this study was to detect marine microorganisms that secrete inhibitory substances against bacteria and microalgae to avoid biofouling on man-made structures in La Paz bay, B.C.S., Mexico. The inhibitory potential of 125 bacteria was evaluated against biofilm-forming bacteria. Crude extracts were obtained with methanol and ethyl acetate from 16 bacterial strains that exhibited antagonistic and antibacterial activity in a preliminary screening. Antibacterial and antimicroalgal assays were performed using crude extracts, the minimum inhibitory concentration (MIC) was determined. The highest activity against bacteria and microalgae was found in two strains, Shewanella algae and Staphylococcus sp. The results of this study suggest that extracts of bacteria from the Gulf of California with antimicrobial properties against biofilm-forming bacteria can also prevent the adhesion of microalgae, which may control the development of biofilm formation and, as a consequence, biofouling.